Amino Azaxylylenes Photogenerated from o‐Amido Imines: Photoassisted Access to Complex Spiro‐Poly‐Heterocycles. Issue 39 (30th June 2015) - Mukhina, Olga A.; Kuznetsov, Dmitry M.; Cowger, Teresa M.; Kutateladze, Andrei G.
Abstract: Upon irradiation, cyclic imines containing o ‐amido groups are shown to produce reactive intermediates, amino azaxylylenes, which undergo intramolecular cycloadditions to tethered unsaturated pendants to yield complex N, O‐heterocycles having an additional spiro‐connected nitrogen heterocyclic moiety. Modular assembly of the photoprecursors allows expeditious increase of the complexity of the target poly‐heterocyclic scaffolds with a minimal number of experimentally simple reaction steps. The photocyclization and subsequent postphotochemical transformations are accompanied by an increase of Lovering's fsp3 factor, thus producing unprecedented three‐dimensional molecular architectures, and offering extended sampling of chemical space. Abstract : Rings in three dimensions : Cyclic imines containing an o ‐amido group undergo excited‐state intramolecular proton transfer to generate amino azaxylylenes. The amino azaxylylenes undergo intramolecular cycloadditions to tethered unsaturated pendants to yield complex heterocyclic three‐dimensional molecular architectures.